STATE OWNED ENTERPRISES (BUMN) REFORM IN INDONESIA: PRIVATIZATION FAILURES - Efiyanti, MA, Alfiana Yuli (IQTISHODUNA, 2008)
It is realized that State Owned Enterprises (BUMN) is one of the most important asset of Indonesia.Â  Those firms are expected to contribute and generate a significant number of revenue.Â  They are also demanded as a public needs provider.Â  However, there are many evidents that the performance of BUMN, that historically heritage from the Dutch colonialist, is not satisfactory. Â  In 1982 when Indonesian economy suffered because of the sharp fall in oil prices, issues regarding the inefficiency of BUMN were widespread due to the lack of their performance.Â  As a result, the government instructed all ministries to increase the productivities and efficiency of BUMN in their departments. Some restructuring and reforming programs including privatization have taken place.Â  However, without any clear objectives, the program was not seriously monitored. Only in mid 1997, when the Asian crises hit Indonesia economy, government needs tool in stabilizing and restructuring the economy.Â  Privatization program then emerged and was not postponed. This report of research presents the failure of privatization program that was adopted during the Asian Crises.Â  It is judged as a failure because the â€œbig bangâ€ action,Â  did not meet both the government written objectives and the theories of privatization.